IL‐15 and IL‐23 synergize to trigger Th17 response by CLA+ T cells in psoriasis. Issue 7 (31st May 2020) - de Jesús‐Gil, Carmen; Ruiz‐Romeu, Ester; Ferran, Marta; Sagristà, Marc; Chiriac, Anca; García, Pablo; Celada, Antonio; Pujol, Ramon M.; Santamaria‐Babí, Luis F.
Abstract: IL‐15 has emerged as a potentially relevant target in the IL‐17 response in psoriasis. However, its mechanism is poorly characterized in humans. IL‐15 and IL‐23 are constitutively expressed in the psoriatic lesion. Also, IL‐15 is considered a susceptibility‐associated gene in psoriasis, as are IL‐23R, and HLACW6 . Here, we studied the effect of IL‐15 and IL‐23 stimulation on the cytokine response of CLA+/CLA‐ T cells from 9 psoriasis patients and 3 healthy control subjects. To this end, CLA + and CLA‐ T cells from blood samples were cultured with epidermal cells from skin biopsies and treated with IL‐15 and IL‐23. After five days of culture, cytokines in supernatant were measured by ELISA or fluorescent bead‐based immunoassay. There was a statistically significant increase in IL‐17F and IL‐17A production ( P < .001) in cocultures of psoriasis skin‐homing CLA + T cells with epidermal cells when stimulated with IL‐15 and IL‐23, but this effect was not observed in the cells of healthy controls. Interestingly, this response was reduced by around 50 to 80% by blocking HLA class I and II molecules. Our results point to the synergic action of IL‐15 and IL‐23 selectively for CLA + cells in psoriasis, leading to the induction of Th17 cell‐related cytokines.